Intersection of Islamic Values and Consumer Preferences - Pradhita, Dewi (Advances in Business & Industrial Marketing Research, 2024)
This study aims to explore the intersection of Islamic values and consumer preferences within the realm of marketing, particularly focusing on the implications for businesses operating in Muslim-majority markets or targeting Muslim consumers worldwide. The research design adopts a qualitative approach, utilizing thematic analysis to synthesize recent literature on Islamic marketing and consumer behavior. The findings reveal that Islamic principles such as halal authenticity, ethical considerations, and cultural sensitivity significantly influence consumer decision-making processes across various product categories. Additionally, the study highlights the growing importance of understanding the impact of technological advancements, regulatory developments, and socio-cultural shifts on consumer behavior and market dynamics within the context of Islamic marketing. The implications of these findings underscore the need for businesses to prioritize halal authenticity, ethical sourcing, and cultural sensitivity in their marketing strategies to build trust, credibility, and loyalty within Muslim communities. This study contributes to the advancement of theory and practice in Islamic marketing, informing strategic decision-making and promoting inclusive and ethical approaches to consumer engagement in the global marketplace.